The clinical outcomes of amoxicillin/clavulanate plus doxycycline versus amoxicillin/clavulanate plus azithromycin for community acquired pneumonia in cardiovascular disease patients / Norhidayah Kasiman @ Kamisan - Kasiman @ Kamisan, Norhidayah (2016)
Objective: This study was conducted to compare the clinical outcomes between amoxicillin/clavulanate plus doxycycline (AC-D) and amoxicillin/clavulanate plus azithromycin (AC-A) in cardiovascular disease patients. Methods: This was a retrospective medical review study of 282 patients with mild to moderate community acquired pneumonia (CAP) admitted in general medical wards, Hospital Sultanah Nora Ismail (HSNI) from January 2014 until August 2015. Patients were divided equally into two groups based on antibiotics received within the first 48 hours of ward admission. Patient demographics, initial laboratory findings, antibiotic therapy, daily vital signs and relevant clinical outcomes were extracted from medical records. Clinical outcomes were compared between two groups of antibiotics by using appropriate statistical tests. Results: Compared to the patients treated with AC-A, those treated with AC-D had similar in time to reach clinical stability (2.32 vs. 2.12 days, p = 0.24), time to switch therapy (3.04 vs. 2.80 days, p = 0.20), hospital LOS (3.15 vs. 2.88 days, p = 0.23), rate of treatment failure (1.4% vs. 2.1%, p = 1.00), number of patients who developed QT prolongation (0% vs. 0.7%, p = 1.00) and early achievement in overall clinical outcomes (64.5% vs. 67.6%, p = 0.58). Conclusions: The use of AC-D in cardiovascular disease patients is non-inferior to AC-A. Based on these findings, the clinical effectiveness of AC-D should be evaluated prospectively.